The Effect of Corner Radius of Square Thin-Walled Structures on Crashworthiness Indicators - Jos Istiyanto; Harry Purnama; Joko Triwardono; Jekki Hendrawan (Majalah Ilmiah Pengkajian Industri, 2022)
Generally, the crash box on automobile vehicles is a thin-walled structure with a square cross-section. The majority of research was carried out for a long time to find the optimum crashworthiness indicator. In this study, numerical simulations and experimental tests are used to investigate the effect of the corner radius of a square cross-section thin-walled structure on crashworthiness indicators. Quasi-static analysis with mild steel material produces the mean force (Pm) error value is less than 3% while varying the corner radius ranging from zero to 1 mm, 2 mm, and 3 mm shows energy absorption (EA) and peak force (Pmax) decreased. Keyword: Thin-walled square tube, Mild steel, Numerical simulation, Experimental test, Crashworthiness indicators.